2017
DOI: 10.1186/s12935-017-0418-6
|View full text |Cite
|
Sign up to set email alerts
|

Metformin exhibits the anti-proliferation and anti-invasion effects in hepatocellular carcinoma cells after insufficient radiofrequency ablation

Abstract: BackgroundThe mechanisms and prevention of progression of hepatocellular carcinoma (HCC) after insufficient radiofrequency ablation (RFA) has been preliminarily investigated, therefore, new strategy needs to be investigated to prevent the process. Whether metformin could be used to inhibit the growth of HCC after insufficient RFA and further prevent the progression of residual HCC remains unclearly.MethodsMTT assay, colony formation assay and transwell assay were used to observe the cell viability, migration a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 35 publications
1
19
0
Order By: Relevance
“…These results are in accordance with those from a study by Valaee et al ( 36 ), indicating that metformin suppresses the proliferation and viability of AGS cells. An in vivo study also demonstrated that metformin did not cause apparent toxicity in nude mice bearing with hepatocellular carcinoma tumors ( 65 ). The findings also revealed that metformin has no effect on viability in normal cells (human colon CCD 841 CoN, embryonic lung HEL 299 and 293 cells).…”
Section: Discussionmentioning
confidence: 99%
“…These results are in accordance with those from a study by Valaee et al ( 36 ), indicating that metformin suppresses the proliferation and viability of AGS cells. An in vivo study also demonstrated that metformin did not cause apparent toxicity in nude mice bearing with hepatocellular carcinoma tumors ( 65 ). The findings also revealed that metformin has no effect on viability in normal cells (human colon CCD 841 CoN, embryonic lung HEL 299 and 293 cells).…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al suggested that metformin could block the proliferation and invasion of HCC cells after insufficient radiofrequency ablation. This effect of metformin could be associated with the suppression of Akt survival signaling through AMPK/PTEN [109].…”
Section: Ampk Activators In Hcc Treatmentmentioning
confidence: 99%
“…For instance, sorafenib and IFN-α combined with herbal compound inhibited the EMT of HCC cells after iRFA ( 28 , 29 ); bevacizumab inhibited the tumor growth and angiogenesis induced by iRFA ( 30 ); and CTLA-4 blockade suppressed the growth of residual tumors and improved survival in a subcutaneous murine HCC model ( 31 ). Other agents include metformin ( 32 ) and hydroxychloroquine (HCQ) ( 33 ). However, one study demonstrated that ATPase inhibitory factor 1 (IF1) increased HCC cells’ resistance to sorafenib after iRFA ( 16 ).…”
Section: Ablation Therapymentioning
confidence: 99%